Ebola Virus Disease Epidemic: What Can the World Learn and Not Learn from West Africa? - Romuladus E. Azuine, DrPH, RN; Sussan E. Ekejiuba, DVM, PhD; Gopal K. Singh, PhD; Magnus A. Azuine, PhD (Global Health and Education Projects, Inc., 2015)
WITH over 4,500 deaths and counting, and new cases identified in two developed countries that are struggling and faltering in their handling of the epidemic, the 2014 Ebola Virus Disease (EVD) epidemic is unlike any of its kind ever encountered. The ability of some poor, resource-limited, developing countries in sub-Saharan Africa to efficiently handle the epidemic within their shores provides some lessons learned for the global health community. Among others, the 2014 EVD epidemic teaches us that it is time to put the "P" back in public and population health around the world. The global health community must support a sustainable strategy to mitigate Ebola virus and other epidemics both within and outside their shores, even after the cameras are gone. Ebola virus must not be called the disease of the poor and developing world.